Intermittent hypoxia: linkage between OSAS and epilepsy - Ma, Yue; Wu, Qiong (Frontiers in Pharmacology, 2023)
Obstructive sleep apnea syndrome (OSAS) refers to the current apnea during sleep caused by upper airway collapse. Meanwhile, epilepsy is a common neurological disorder with a tendency for spontaneous and persistent seizures. Accumulating evidence indicates that OSAS was not independent of epilepsy. Patients with OSAS were observed to be susceptible to epilepsy, while OSAS could decrease the seizure threshold in epilepsy. However, the mechanisms underlying the association of OSAS with epilepsy have not been fully understood. In this study, we propose that intermittent hypoxia, common among OSAS patients due to upper airway collapse, is the linkage between OSAS and epilepsy.Intermittent hypoxia induces elevated levels of oxidative stress and inflammation, potentially causing excessive inflammatory and endoplasmic reticulum stress in brain tissue, which might ultimately lead to the development of epilepsy. Therapeutic approaches targeting inflammation and oxidative stress may provide novel insights into the treatment of OSAS and epilepsy.